The Intersection of the Genetic Architectures of Orofacial Clefts and Normal Facial Variation - Indencleef, Karlijne; Hoskens, Hanne; Lee, Myoung Keun; White, Julie D.; Liu, Chenxing; Eller, Ryan J.; Naqvi, Sahin; Wehby, George L.; Moreno Uribe, Lina M.; Hecht, Jacqueline T.; Long, Ross E.; Christensen, Kaare; et al. (Frontiers in Genetics, 2021)
Unaffected relatives of individuals with non-syndromic cleft lip with or without cleft palate (NSCL/P) show distinctive facial features. The presence of this facial endophenotype is potentially an expression of underlying genetic susceptibility to NSCL/P in the larger unselected population. To explore this hypothesis, we first partitioned the face into 63 partially overlapping regions representing global-to-local facial morphology, and then defined endophenotypic traits by contrasting the 3D facial images from 264 unaffected parents of individuals with NSCL/P versus 3,171 controls. We observed distinct facial features between parents and controls across 59 global-to-local facial segments at nominal significance (p<=0.05) and 52 segments at Bonferroni corrected significance (p<1.2x10-3), respectively. Next, we quantified these distinct facial features as univariate traits in another dataset of 8,246 unaffected European individuals and performed a genome-wide association study. We identified 29 independent genetic loci that were associated (p<5x10-8) with at least one of the tested endophenotypic traits, nine genetic loci also passed the study-wide threshold (p<8.47x10-10). Of the 29 loci, 22 were in proximity of loci previously associated with normal facial variation, 18 were near genes that show strong evidence in orofacial clefting, and another 10 showed some evidence in orofacial clefting. Additionally, polygenic risk scores for NSCL/P showed associations with the endophenotypic traits. This study thus supports the hypothesis of a shared genetic architecture of normal facial development and orofacial clefting.